Cruise tourism in the Arctic : sustainability issues and protection of the marine environment in international law - Nordblom, Ulrika, 1986- (2016)
Climate change has made the Arctic famous, drawing attention to it both as a source of non-renewable natural resources and as an area in need of environmental conservation. The physical accessibility of the region has increased together with this rising interest, and a growing number of tourists are keen to get a glance at its icy scenery and unique wildlife while they are still there to be explored. Increased traffic in the region, however, brings with it increasing pollution, the threat of invasive species, the risk of accidents and a demand for up-to-date infrastructure. These factors create stresses upon the local environment and on economies that are highly dependent on natural resources, while also accelerating global climate change. Some tourists choose to travel by cruise ships that make them a contributor to the changes facing the Arctic, but also isolate them from the local markets as all service is provided on board. Arctic cruise tourism can therefore be said to be degrading the conditions at its destination but making little contribution to financially compensate for the environmental damage it causes. The international law of the sea concerns cruise vessels just as it does all marine traffic. Yet existing environmental standards fail to provide a sufficient level of protection and enforcement to guarantee the sustainability of cruise shipping in the Arctic. While the principles of international environmental law should lead the prescription of norms, economic pressures affect the political process. The Antarctic has environmental characteristics and faces challenges for the enforcement of regulations similar to those in the Arctic, but has for a long time enjoyed a better standard of conservation under its own treaty system. The Polar Code adopted in 2015 is the first step towards uniform regulation of both polar regions and provides the first set of environmental standards for the Arctic that take into account the special features of the region. The development of environmental standards and ...